A new tripodal ligand system with steric and electronic modularity for uranium coordination chemistry - Bart, Suzanne C.; Heinemann, Frank Wilhelm; Anthon, Christian; Hauser, Christina; Meyer, Karsten (Inorganic Chemistry, 2009)
The synthesis of a potentially redox active tripodal ligand containing a tris(aryloxide) functionalized mesitylene anchor, (( ArOH) mes) (1), and its metalation with low-valent uranium to form [(( ArO) mes)U] (1-U) Is reported. The results from characterization by X-ray crystallography, spectroscopic studies, and computational analysis, as well as Initial reactivity studies, support a +3 uranium oxidation state. Comparison to the previously synthesized complex, [(( ArO) tacn)U] (2-U), featuring the redox-lnnocent triazacyclononane anchor reveals that changing the anchor from the flexible trlazacyclononane to a rigid mesityl fragment increases the structural flexibility of the aryloxide substituents in complexes of 1. The synthesis and crystal structures of uranium(IV) amide complexes of 1-U and 2-U are discussed. © 2009 American Chemical Society.